Appraising performance appraisal - Loh, Charles Chen Hwee (2014)
Being an important element of information and control, performance appraisal has been receiving considerable attention, especially in large, complex organizations. In order to survive in today's highly competitive global market, it is essential for organizations to employ good appraisal programs for the purpose of effective human resource management.